Design of a wasp-inspired biopsy needle capable of self-propulsion and friction-based tissue transport - Bloemberg, Jette; van Wees, Suzanne; Kortman, Vera G.; Sakes, Aimée (Frontiers in Bioengineering and Biotechnology, 2025)
Percutaneous pancreatic core biopsy is conclusive but challenging due to large-diameter needles, while smaller-diameter needles used in aspiration methods suffer from buckling and clogging. Inspired by the ovipositor of parasitic wasps, which resists buckling through self-propulsion and prevents clogging via friction-based transport, research has led to the integration of these functionalities into multi-segment needle designs or tissue transport system designs. This study aimed to combine these wasp-inspired functionalities into a single biopsy needle by changing the interconnection of the needle segments. The resulting biopsy needle features six parallel needle segments interconnected by a ring passing through slots along the length of the needle segments, enabling a wasp-inspired reciprocating motion. Actuation employs a cam and follower mechanism for controlled translation of the segments. The needle prototype, constructed from nitinol rods and stainless steel rings, measures 3 mm in outer diameter and 1 mm in inner diameter. Testing in gelatin phantoms demonstrated efficient gelatin core transport (up to 69.9% ± 9.1% transport efficiency) and self-propulsion (0.842 ± 0.042 slip ratio). Future iterations should aim to reduce the outer diameter while maintaining tissue yield. The design offers a promising new avenue for wasp-inspired medical tools, potentially enhancing early pancreatic cancer detection, thus reducing healthcare costs and patient complications.